Design and Structure Analysis of a CNC Laser Engraver Machine - Asmara Yanto; Anrinal; Irfan Mandala Putra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
This study aims to design a CNC machine to perform the laser engraving process (called the CNC Laser Engraver Machine). The design stage starts from the laser module unit as an input at the design stage of the 3-Axis CNC Machine to drive the laser. The main geometry of the machine is designed referred to the laser position i.e. workspace and laser height with respect to the engraving table. Then the geometry of the Z-Axis unidirectional laser drive unit is determined to assist when adjusting the laser height of the engraving table. Then the geometry of the laser drive unit in the direction of X-Axis and Y-Axis is designed to move on the engraving area, and then the geometry of the engraving table is designed. After the design is complete, the design is validated by analyzing the structure of the machine based on the conditions and workload of the machine to obtain the appropriate dimensions and materials. The design and structure analysis of the CNC Laser Engraver Machine is carried out by using the CAD software. The design results of the CNC Laser Engraver Machine consist of 5 units i.e. Laser Engraver Module Unit, Z-Axis Unit, X-Axis Unit, Y-Axis Unit and Engraving Table Unit which are mounted with a bolt system. This CNC Laser Engraver machine designed has a workspace of 310 mm x 390 mm in the X-Y plane with the laser height in the Z-Axis direction can be adjusted 10 mm to 60 mm above the engraving table. The total dimensions of this CNC Laser Engraver Machine are 585 mm x 533 mm x 350 mm with a total weight about 22 kg.